2013
DOI: 10.1080/0098261x.2013.10768044
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Between-Judge Disparities in Imprisonment Decisions Across Sentencing Regimes in Ohio

Abstract: Empirical studies of judicial effects on the use of imprisonment have yet to estimate changes in these effects under more-structured sentencing schemes. Findings are presented from a multilevel analysis of whether the implementation of Ohio's presumptive guidelines in 1996 was effective for reducing inter-judge differences in the distribution of non-suspended prison sentences and in defendant-level effects on imprisonment. These data for seven urban courts provide a unique opportunity to estimate changes in ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Probationers in front of Judges B and C were less likely to be sanctioned, regardless of the nature and extent of noncompliance. These results are not surprising, considering the evidence of inter-judge disparity in sentencing decisions, yet it suggests that judges may view their role as agents of accountability differently (Anderson & Spohn, 2010; Kim, Spohn, & Hedberg, 2015; Wooldredge, Griffin, & Thistlethewaite, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…Probationers in front of Judges B and C were less likely to be sanctioned, regardless of the nature and extent of noncompliance. These results are not surprising, considering the evidence of inter-judge disparity in sentencing decisions, yet it suggests that judges may view their role as agents of accountability differently (Anderson & Spohn, 2010; Kim, Spohn, & Hedberg, 2015; Wooldredge, Griffin, & Thistlethewaite, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…These studies have demonstrated mixed findings in variations of sentencing practices across judges. Some have found that judges of color sentence more leniently (Johnson, 2006; Johnson & DiPietro, 2012) and others find no difference (Wooldredge et al., 2013). Similarly, a few studies find sex differences in sentencing practices of judges, while others find no effect (Johnson & DiPietro, 2012; Wooldredge et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some have found that judges of color sentence more leniently (Johnson, 2006; Johnson & DiPietro, 2012) and others find no difference (Wooldredge et al., 2013). Similarly, a few studies find sex differences in sentencing practices of judges, while others find no effect (Johnson & DiPietro, 2012; Wooldredge et al., 2013). One study found that older judges tend to sentence more leniently (Johnson, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, past research has found that judicial decisions are affected by a myriad of extra-legal factors such as those related to the personal characteristics of the defendant or plaintiff including his/her gender, race and age (e.g., Doerner & Demuth, 2010;Manning, Carroll, & Carp, 2004;Mitchell, 2005;Rachlinski, Johnson, Wistrich, & Guthrie, 2009;Robbennolt, 2002;Turner & Johnson, 2006). Judges' own gender, race and age have also been found to influence their decisions (e.g., Wooldredge, Griffin, & Thistlethwaite, 2013;Chew & Kelley, 2008;Coontz, 2000;Kulik, Perry, & Pepper, 2003;Martin & Pyle, 2004;Peresie, 2004). Studies have also demonstrated that judicial decisions are distorted by cognitive illusions such as framing effects, anchoring, and hindsight bias (e.g., Englich, Mussweiler, & Strack, 2006;Guthrie, Rachlinski, & Wistrich, 2001;Hastie & Viscusi, 1998;Rachlinski, Guthrie, & Wistrich, 2011) and biased by non-cognitive factors such as hunger (Danziger, Levav, & Avnaim-Pesso, 2011).…”
mentioning
confidence: 99%